Pengembangan Media Video Tutorial Pembuatan Desain Busana Pesta di Fase F SMK Negeri 1 Wonoasri - Haryati, Jasmine; Deny Arifiana; Marniati Marniati (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aimed to describe the feasibility level of the video tutorial for creating evening gown designs in Phase F at SMK Negeri 1 Wonoasri and to examine students’ learning outcomes after its implementation. This research employed a research and development (R&D) method using the ADDIE model. Data were collected through validation sheets assessed by three material experts, three media experts, and three language experts, as well as performance tests. The data were analyzed using descriptive statistics, including the calculation of average validation scores and learning mastery percentages. The results indicated that the video tutorial achieved a validity level of 96.1%, categorized as highly feasible, and the learning mastery reached 86.11%.